Javanese Gamelan as Sacred Manifestation: Exploring Its Role in Catholic Liturgical Inculturation and Spiritual Dialogue - Pius Pandor; Sekundus Septo Pigang Ton; Petrus Yuniarto; Heribertus Heribertus (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2025)
Javanese gamelan, a traditional musical ensemble deeply embedded in Javanese culture, serves as a profound symbol of harmony and spiritual values, reflecting principles such as balance, restraint, and tolerance. Historically integral to religious and ceremonial contexts, gamelan embodies a sacred medium through which the Javanese engage with the Divine, aligning with Mircea Eliade’s concept of hierophany—the manifestation of the sacred in the profane world. Despite its rich cultural and philosophical significance, contemporary shifts have led to a decline in gamelan’s popularity and its associated values, impacting cultural practices including the inculturation process within the Catholic Church among Javanese communities. This qualitative study, based on interviews, observations, and literature review, demonstrates that gamelan transcends mere musical function, offering a theological and cultural framework that can enhance Catholic liturgical music. Integrating gamelan into worship not only enriches faith expression but also fosters cultural identity and supports liturgical inculturation. The findings contribute to the discourse on cultural heritage preservation and religious adaptation by proposing a model that harmonises local artistic traditions with Christian worship, encouraging further interdisciplinary research and practical application.